2013
DOI: 10.1177/0894318413489180
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Prenatal Health Behaviors of Women from Four Cultural Groups in Turkey

Abstract: This research was conducted to uncover women's health behaviors during prenatal periods using a transcultural approach. The qualitative ethnonursing method was used, and the research was conducted at the family health center in Bornova District in Izmir. The data were collected between November 2007 and August 2008 using the purposive sampling method. Eighteen pregnant women were included in the study and in-depth face-to-face semi-structured interviews were recorded on an audio recording device. A thematic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Including awakening sense of (nonreligious) spirituality. In some cases, fatalism (adverse outcomes are 'Gods will') Biomedical/clinical 1,4,5,6,7,8,9,10,14,15,16,20,23,24,30,31,33,35,37 Turkey ( 4,5,7,9,12,13,14,15,16,20,30,31,36,37 Vietnam We also propose that provision of information in pregnancy should include physiological, behavioural, social, cultural and biomedical components, and it should value embodied and cultural knowledge, as well as biomedical evidence. It should be tailored to the needs of the particular woman at the specific time in her pregnancy when that particular information is needed, and it should be given in a manner and through a medium that is comprehensible and accessible for her.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Including awakening sense of (nonreligious) spirituality. In some cases, fatalism (adverse outcomes are 'Gods will') Biomedical/clinical 1,4,5,6,7,8,9,10,14,15,16,20,23,24,30,31,33,35,37 Turkey ( 4,5,7,9,12,13,14,15,16,20,30,31,36,37 Vietnam We also propose that provision of information in pregnancy should include physiological, behavioural, social, cultural and biomedical components, and it should value embodied and cultural knowledge, as well as biomedical evidence. It should be tailored to the needs of the particular woman at the specific time in her pregnancy when that particular information is needed, and it should be given in a manner and through a medium that is comprehensible and accessible for her.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from the included studies at step three (studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] were then mapped to the amended framework to check that all the themes continue to have explanatory power, and to make sure no themes were missing [text in red in Tables 1 and 2, and in the (Table S2) represent the studies identified in step three]. As in the planned analytic strategy, this comprised both a reciprocal process (when the data could be mapped to the framework) and a refutational one (to check if any of the data could not be mapped).…”
Section: Characteristics and Quality Of Included Studiesmentioning
confidence: 99%
“…Bonadio (15) São Paulo city, Brazil Prenatal Service of a Philanthropic Institution Not cited A Woodward (16) Not informed Hospital and maternity hospital of a national health service 12 visits A Berry (17) Southwestern United States Prenatal public health clinic, a hospital and households 11 months A Nahas and Amasheh (18) Western Sydney Area, Australia Community Not cited A Morin et al (19) United States Middle Atlantic Region Maternal and child unit of a small community hospital 12 months A Angus et al (20) Uninformed Four community hospitals 20 days A Praça (21) West zone of the municipality of São Paulo, Brazil Community center and slum households 19 months A Hoga (22) São Paulo, Brazil Child birth center 5 months A Jeneral and Hoga (23) Sorocaba city, interior of São Paulo state, Brazil Low income community Not cited A Medves and Davies (24) Ontario, Canada Rural maternity hospital Not cited A Bezerra and Cardoso (25) Fortaleza, Ceará, Brazil Inpatient unit and obstetric center of public maternity and households 3 months A Monticelli and Elsen (26) South region of Brazil Collective unit of public maternity joint housing 12 months A Monticelli and Elsen (27) South region of Brazil Collective unit of public maternity joint housing 12 months A Bezerra and Cardoso (28) Fortaleza, Ceará, Brazil Inpatient unit and public maternity obstetric center 3 months A Foster et al (29) Dominican Republic Reference hospital and maternity hospital Not cited A El-Nemer et al (30) Egypt Hospital and maternity 3 months A Kennedy and Lyndon (31) Northern California, United States Northern California Urban Teaching Hospital 24 months A Leal and Rodríguez (32) Girardot City, Colombia Hospital Prenatal Care Program 3 months A Bernal-Roldán et al (33) Suba and Ciudad Bolivar Localities, Bogota City, Colombia Households Not cited A MacKinnon (34) Cranbrook city, Western Province of British Columbia, Canada Rural Regional Hospital 48 months A MacKinnon (35) Cranbrook city, Western Province of British Columbia, Canada Rural Regional Hospital 48 months A Maia and Silva (36) Benjamin Constant City, Amazonas, Brazil Ribeirinha community 2 months A Prieto and Ruiz (37) Tunja City, Boyaca Department, Colombia Households Not cited A Tasçı-Duran and Sevil (38) Bornova, İzmir Province Metropolitan District, Turkey Family Health Center 10 months A Feyer et al…”
Section: Authorship Location Research Scenarios and Contexts Immersiomentioning
confidence: 99%
“…Regarding the theoretical and methodological aspects, Chart 3 presents the summary of the elements found in the selected articles. Among the methodological frameworks adopted were: ethnography (15)(16)(21)(22)29,31,39) , focused ethnography (19)(20)31) , institutional ethnography (24,(34)(35)(40)(41)44) and ethnonursing (17)(18)23,(25)(26)(27)(28)(32)(33)(36)(37)(38)(42)(43) .…”
Section: Authorship Location Research Scenarios and Contexts Immersiomentioning
confidence: 99%
See 1 more Smart Citation